Prevalence of hepatitis antibodies in chronic alcoholics and its importance - Günay ÖNDER; Abidin ALTINAY; Belkıs ÜNSAL; Nafi YAZICIOĞLU; Bülent KARA; Kadir AKSÖZ; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-